2018
DOI: 10.3892/ol.2018.8779
|View full text |Cite|
|
Sign up to set email alerts
|

EZH2 inhibition promotes methyl jasmonate‑induced apoptosis of human colorectal cancer through the Wnt/β‑catenin pathway

Abstract: Abstract. Methyl jasmonate potentially induces the differentiation of human myeloid leukemia cells and inhibits their proliferation; it may induce the differentiation and apoptosis of human lymphocytic leukemia cells, but does not exert a damaging effect on normal lymphocytes. In the present study, the anticancer effect of methyl jasmonate on human colorectal cancer cells was investigated. Cell viability and apoptosis was assessed using a Cell Counting kit-8 assay and flow cytometry, respectively. Methyl jasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…The abnormal expression or activation of EZH2 is related to the pathogenesis of AKI Zhou et al, 2018b ). Initially, it was found that EZH2 is involved in many cellular responses, such as apoptosis and inflammation ( Wang Y. et al, 2018 ; Bamidele et al, 2019 ). The expression of EZH2 and H3K27me3 is up-regulated in ischemia-reperfusion and folic acid-induced AKI models ( Zhou et al, 2018b ).…”
Section: Ezh2 and Acute Kidney Injurymentioning
confidence: 99%
“…The abnormal expression or activation of EZH2 is related to the pathogenesis of AKI Zhou et al, 2018b ). Initially, it was found that EZH2 is involved in many cellular responses, such as apoptosis and inflammation ( Wang Y. et al, 2018 ; Bamidele et al, 2019 ). The expression of EZH2 and H3K27me3 is up-regulated in ischemia-reperfusion and folic acid-induced AKI models ( Zhou et al, 2018b ).…”
Section: Ezh2 and Acute Kidney Injurymentioning
confidence: 99%
“…In the Sham + DZNeP (Selleck, S7120) group, mice were administrated with DZNeP (0.5, 1.0, and 2.5 mg/kg) by intraperitoneal injection for 5 consecutive days before sham operation, once a day. In I/R group, the left renal vessels were blocked using a clamp for 30 min followed by various reperfusion time (6,12,24 h) without any treatments. In I/R + DZNeP group, mice were administrated with DZNeP (0.5, 1.0, and 2.5 mg/kg) by intraperitoneal injection for 5 consecutive days before I/R model established.…”
Section: Experimental Mice and Establishment Of Renal I/r Injurymentioning
confidence: 99%
“…6 Enhancer of zeste homolog 2 (EZH2), a type of histone methyltransferases, is well known as the main catalytic part of polycomb repressive complex 2 (PRC2) and plays a vital role in triggering trimethylation of histone H3 at lysine27, which has been reported to be involved in the progression of a variety of kidney disease models, including renal I/R injury. 11,12 However, the underlying mechanisms and roles of EZH2 in renal I/R injury have not been totally elucidated. 10 Simultaneously, numerous evidences demonstrated that EZH2 was linked to a variety of cellular responses, such as apoptosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The broad-spectrum anticancer action of MJ has been vividly demonstrated against neoplastic cells of diverse origins (1,2). The cytotoxic activity of MJ against neoplastic cells has been shown to implicate a wide variety of molecular mechanisms but majorly through the induction of mitochondrial-mediated apoptotic cell death by involving altered functions of mitochondria (3,4) and causing detachment of hexokinase from VADC (5). However, the bulk of data associated with MJ's antineoplastic action is mainly from in vitro studies performed against a wide variety of neoplastic cell lines (1,2,6,7).…”
Section: Introductionmentioning
confidence: 99%